2005
DOI: 10.1086/426819
|View full text |Cite
|
Sign up to set email alerts
|

Possible Animal Origin of Human-Associated, Multidrug-Resistant, Uropathogenic Escherichia coli

Abstract: These observations suggest that drug-resistant, uropathogenic human-associated E. coli strains potentially have an animal origin. The possibility that human drug-resistant UTI could be a foodborne illness has serious public health implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
113
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(126 citation statements)
references
References 26 publications
9
113
1
3
Order By: Relevance
“…Although this isolate's virulence profile resembled that of the outbreak isolates, including the EAEC genes, the isolate differed from the outbreak isolates according to astA status (positive), biotype (D), and PFGE profile (data not shown). Thus, although a potential food or animal origin has been proposed for certain human-associated, multidrug-resistant uropathogenic E. coli clonal groups (26,38), and a close relationship has been demonstrated between E. coli from retail chicken meat and E. coli causing human UTI (52), no candidate animal source for the Copenhagen outbreak was identified here.…”
Section: Discussionmentioning
confidence: 92%
“…Although this isolate's virulence profile resembled that of the outbreak isolates, including the EAEC genes, the isolate differed from the outbreak isolates according to astA status (positive), biotype (D), and PFGE profile (data not shown). Thus, although a potential food or animal origin has been proposed for certain human-associated, multidrug-resistant uropathogenic E. coli clonal groups (26,38), and a close relationship has been demonstrated between E. coli from retail chicken meat and E. coli causing human UTI (52), no candidate animal source for the Copenhagen outbreak was identified here.…”
Section: Discussionmentioning
confidence: 92%
“…In recent years, ESBLproducing Enterobacteriaceae isolates have shifted from the hospital to the community and the environment [41]. ESBL-producing Enterobacteriaceae have been recovered from different sources in the community, including cattle, chickens, pigs, raw milk and lettuce [42][43][44]. Recent study from India reported that a substantial number of tap water samples were contaminated with carbapenemase blaNDM-1 producing organisms [45].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, to our knowledge, E. coli O15:K52:H1 has never been isolated from either animals or meat products, although this could simply reflect limited sampling. A potential animal origin of certain human-associated multidrug-resistant uropathogenic E. coli strains has been proposed (18,25) but remains unproven. The absence of animal isolates in the present population argues against a food animal reservoir for E. coli O15:K52:H1.…”
Section: Discussionmentioning
confidence: 99%
“…The study was limited to (i) Danish isolates, regardless of previous publication status, and (ii) previously unpublished isolates from other countries, using one isolate per patient. Seven English, eight Spanish, and three American O15:K52:H1 isolates were excluded by virtue of previous publication (8,24,25), six isolates were duplicates from the same patients (all Danish), and one was subsequently lost (total number excluded, 25). Thus, 100 isolates from 100 different patients infected with E. coli O15:K52:[H1] from 1975 to 2006 were studied.…”
Section: Methodsmentioning
confidence: 99%